Development of the Life Skills Learning Model for Elementary School students as Strengthening the Pancasila Student Profile - Suriswo; Aulia, Fikri; Utami, Wikan Budi (JTP - Jurnal Teknologi Pendidikan, 2023)
This study aims to determine the development of life skills of elementary school students in social science subjects through the development of life skills education. Learning Social Sciences Education certainly gets the spotlight related to the role of the teachers and the conditions of the students. The teacher still holds power in learning, while students can only follow all directions given by the teacher. As a result, students only memorize and do the teacher’s orders. Conditions like this must be changed because it is in accordance with the changing times in the kurikulum merdeka. Learning Social Sciences in schools at various levels of educational development needs to be based on aspects of the curriculum, philosophy and learning theory, as well as various aspects in accordance with the nature of social studies education.. This study uses a research and development (R & D) approach that begins with a preliminary study, followed by limited trials and wider trials, and ends with model validation tests. Limited trials and wider trials which were carried out repeatedly at an elementary school in Tegal City and accompanied by revisions at each trial; and model validation tests were carried out at three elementary schools as the experimental group and three elementary schools as the control group without the presence of the researcher. The focus of development is social studies learning carried out by teachers of class V SD in Tegal City. Data were collected by interview, observation, questionnaire, and learning achievement tests. The model design test is carried out through limited trials and wider trials. Validation of the model design developed using a quasi-experimental design. Data analysis was carried out descriptively, and t-test statistical analysis. The results of the study show that the life skill learning model in social studies learning has improved learning outcomes and students’ life skills so that the profile of Pancasila is strengthened.